Activation of Double-stranded RNA-activated Protein Kinase (PKR) by Interferon-stimulated Gene 15 (ISG15) Modification Down-regulates Protein Translation - Okumura, Fumihiko (American Society for Biochemistry and Molecular Biology, 2013)
The ubiquitin-like molecule ISG15 (UCRP) and protein modification by ISG15 (ISGylation) are strongly induced by interferon, genotoxic stress, and pathogen infection, suggesting that ISG15 plays an important role in innate immune responses. However, how ISGylation contributes to innate immune responses is not clear. The dsRNA-dependent protein kinase (PKR) inhibits translation by phosphorylating eIF2α to exert its anti-viral effect. ISG15 and PKR are induced by interferon, suggesting that a relationship exists between ISGylation and translational regulation. Here, we report that PKR is ISGylated at lysines 69 and 159. ISG15-modified PKR is active in the absence of virus infection and phosphorylates eIF2α to down-regulate protein translation. The present study describes a novel pathway for the activation of PKR and the regulation of protein translation.